Mentha: Nutritional and Health Attributes to Treat Various Ailments Including Cardiovascular Diseases - Saddam Saqib; Fazal Ullah; Muhammad Naeem; Muhammad Younas; Asma Ayaz; Sajid Ali; Wajid Zaman (Molecules, 2022)
A poor diet, resulting in malnutrition, is a critical challenge that leads to a variety of metabolic disorders, including obesity, diabetes, and cardiovascular diseases. Mentha species are famous as therapeutic herbs and have long served as herbal medicine. Recently, the demand for its products, such as herbal drugs, medicines, and natural herbal formulations, has increased significantly. However, the available literature lacks a thorough overview of Mentha phytochemicals’ effects for reducing malnutritional risks against cardiovascular diseases. In this context, we aimed to review the recent advances of Mentha phytochemicals and future challenges for reducing malnutritional risks in cardiovascular patients. Current studies indicated that Mentha species phytochemicals possess unique antimicrobial, antidiabetic, cytotoxic, and antioxidant potential, which can be used as herbal medicine directly or indirectly (such as food ingredients) and are effective in controlling and curing cardiovascular diseases. The presence of aromatic and flavor compounds of Mentha species greatly enhance the nutritional values of the food. Further interdisciplinary investigations are pivotal to explore main volatile compounds, synergistic actions of phytochemicals, organoleptic effects, and stability of Mentha sp. phytochemicals.